Quantum Physics of Atoms, Molecules Solids, Nuclei, and Particles - Eisberg, Robert Resnick, Robert (New Delhi Wiley, 2009)
In simple language, without mathematics, this book explains the strange and exciting ideas that make the subatomic world so different from the world of the every day. It offers the general reader access to one of the greatest discoveries in the history of physics and one of the oustanding intellectual achievements of the twentieth century.
Includes Index and Illustrations.
Keywords: Quantum theory